COVID19 Led Virtualization: Green Data Center for Information Systems Research. Issue 4 (1st October 2020) - Lee, Habin; Choi, Youngseok; Van Nguyen, Truong; Hai, Yang; Kim, Junchul; Bahja, Mohammed; Hocaoğlu, Hakan
ABSTRACT: Recent lockdowns over the world due to COVID19 pandemic accelerated virtualization of our social and work life. While virtualization contributes to reducing green-house-gas (GhG) through reduced mobility, it also dramatically increases energy consumption by data centers (DCs) which host large number of servers for realizing virtualization. This paper argues that current engineering-oriented studies on Green DCs need to be complemented by IS scholars to address human and organizational issues.